2009
DOI: 10.2460/javma.235.11.1314
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between values for arterial and end-tidal partial pressures of carbon dioxide in spontaneously breathing, critically ill dogs

Abstract: Results suggested that nasal capnography is a clinically relevant method of estimating PaCO(2) in spontaneously breathing, critically ill dogs, but that values should be interpreted with caution in dogs receiving supplemental oxygen and in dogs with conditions affecting the respiratory system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 11 publications
2
18
1
Order By: Relevance
“…In this study, the respiratory rate recorded at the T 0 measurement in both groups was observed to be higher than the respiratory rates recorded at subsequent measurements. However, there was no statistically significant difference between respiratory rates obtained at T 15 , T 30 and T 60 in the MV group.…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…In this study, the respiratory rate recorded at the T 0 measurement in both groups was observed to be higher than the respiratory rates recorded at subsequent measurements. However, there was no statistically significant difference between respiratory rates obtained at T 15 , T 30 and T 60 in the MV group.…”
Section: Resultsmentioning
confidence: 52%
“…The effect of measurement time on heart rate was found to be significant in both the SV (P<0.01) and MV groups (P<0.05). In the MV group, it was observed that no statistically significant decrease occurred in the T 15 and T 30 measurements, only that the heart rate measured at T 60 was lower than the heart rate at T 0 . In the SV group, however, a significant decrease compared to the initial measurement was observed at T 30 and, furthermore, an additional drop was seen to occur at T 60 .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations